1976
DOI: 10.1111/j.1365-2222.1976.tb01913.x
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and wheezy bronchitis in children

Abstract: Twice as many boys,as girls are prone to wheeze (15-3% compared with 7%). This study examines the possible immunological basis for this phenomenon. There were 1064 children in this survey. The family of each wheezy child was indexed, and a control sampleof families was selected. At least 85% of the study population were skin tested for Type I allergic reactions. An interval survey of values for FEV,, FVC and PEFR against height was completed.Of 118 wheezy subjects there were 83/542 boys and 35/522 girls. Singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1977
1977
1986
1986

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Immunological status may be one of these shared differences. In an associated study (Davis, 1976), the author has shown that the mothers and fathers of asthmatic children differ from controls in atopic status: 20 % of the parents of asthmatics demonstrated multiple sensitivity on skin testing, compared with 7 % of controls. Of the asthmatic children, 49% of boys and 42% of girls were atopic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunological status may be one of these shared differences. In an associated study (Davis, 1976), the author has shown that the mothers and fathers of asthmatic children differ from controls in atopic status: 20 % of the parents of asthmatics demonstrated multiple sensitivity on skin testing, compared with 7 % of controls. Of the asthmatic children, 49% of boys and 42% of girls were atopic.…”
Section: Discussionmentioning
confidence: 99%
“…As part of the author's work (Davis, 1976), the whole population of index families was subjected to a skin prick testing routine to identify objectively the atopic subjects. Thus the cases male and female, their siblings and their parents were all screened.…”
Section: Methodsmentioning
confidence: 99%
“…This is merely of use in making me more suspicious that any allergy may be of importance in causing the patient's disease. Davis (1976) in his excellent studies on children favours multiple positivity to more than one group of allergens to define atopy. I would agree that such a finding is very significant, but even one positive prick test has been shown to be associated with significantly higher levels of total serum IgE (D'Souza & Davies, 1977).…”
Section: Allergic Diagnosismentioning
confidence: 99%